Model of educational assurance participation in small schools in Thailand - Somchai Posri; Pacharawit Chansirisira (Journal of Education and Learning (EduLearn), 2026)
This study investigates stakeholder participation in educational quality assurance (QA) for small schools in Thailand. The primary objective is to identify key components and indicators of participation and to bridge the gap between current and desired engagement levels. The study delineates five participation components and 13 indicators, providing a comprehensive framework for evaluating and enhancing stakeholder involvement. We employed a mixed-methods research design, incorporating group discussions, questionnaires, interviews, and model assessments to collect data from stakeholders in small schools in northeastern Thailand. We used basic statistical techniques to analyze the data, revealing that current participation is moderate, while the desired level is substantially higher. The participatory model developed in this study was operationalized through an 84-hour training program aimed at strengthening collaboration among administrators, teachers, and community members. The study also discusses other problems, like limited infrastructure and the possible addition of digital tools that could help with engagement even more. These results show how important it is for stakeholders to be involved in ensuring the quality of education. They also give us useful information for future research and policymaking that aims to improve education in small schools.